2012
DOI: 10.1055/s-0032-1324705
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Resection of Adnexal Masses during Pregnancy

Abstract: Robotic resection of adnexal masses during pregnancy appears both safe and feasible, with similar surgical outcomes when compared with a historic laparoscopic cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Several aspects of surgical planning are important to consider, and these include surgical approach (laparoscopy versus laparotomy), patient positioning to optimize patient hemodynamics, entry approach and location, use of carbon dioxide gas for peritoneal insufflation, uterine and adnexal manipulation, and choice of anesthesia. Although some studies have reported the use of robotic surgery for adnexal masses in pregnancy [19], no significant advantage over laparoscopy has been demonstrated. As previously mentioned, historically the preferred surgical approach is by laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Several aspects of surgical planning are important to consider, and these include surgical approach (laparoscopy versus laparotomy), patient positioning to optimize patient hemodynamics, entry approach and location, use of carbon dioxide gas for peritoneal insufflation, uterine and adnexal manipulation, and choice of anesthesia. Although some studies have reported the use of robotic surgery for adnexal masses in pregnancy [19], no significant advantage over laparoscopy has been demonstrated. As previously mentioned, historically the preferred surgical approach is by laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Eichelberger et al further compared the surgical and obstetric outcomes for robotic surgery with laparoscopic dissection of adnexal masses during pregnancy; the robotic surgery showed a significantly shorter length of hospital stay and blood loss [14]. However, cases of complete surgical staging procedure performed during pregnancy had not been illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences in operative time, intraoperative or postoperative complications, or obstetrical outcomes. 106 While there are limited data on robotic surgery in pregnancy, it appears to be both safe and feasible with comparable surgical and obstetrical outcomes.…”
Section: Surgical Approachmentioning
confidence: 99%
“…Eichelberger et al 106 examined the safety and feasibility of robotic-assisted resection of adnexal masses and compared surgical and obstetric outcomes of robotic versus laparoscopic removal. Patients who underwent robotic resection had a significantly shorter hospital stay and decreased blood loss.…”
Section: Surgical Approachmentioning
confidence: 99%